Manajemen pemasaran digital dan intensifikasi budidaya ayam kampung pada Kelompok Ternak Tamansari, Kecamatan Jaken, Kabupaten Pati - Muhammad Sultan Mubarok; Syamsul Arifin; Muhammad Taufiq Abadi (Nur Science Institute, 2026)
This community service program focused on digital marketing management and intensification of native chicken farming within the Tamansari Livestock Group in Jaken District, Pati Regency. The program involved four core participants, purposively selected from the livestock group, and was implemented through a participatory approach comprising socialization, Focus Group Discussion, training, technical assistance, monitoring, and evaluation. The activity began with the identification of farmers’ problems in managing native chicken farming, followed by training on egg hatching, the provision of parent stock, improvements in brooding management, the provision of cages, and the strengthening of parent-stock housing management. Participants were also trained to formulate native chicken rations using locally available materials, including agricultural waste and nutrient-rich plant leaves. The program also included vaccination training, preparation of herbal remedies for chicken health, and assistance in creating Google My Business and Facebook Marketplace accounts. The evaluation results showed that the program improved participants’ awareness, knowledge, and practical skills in managing native chicken farming more intensively, while also creating initial opportunities to expand market access through digital platforms